Can polymer coils Be modeled as "Soft colloids"? - Louis, A; Bolhuis, P; Hansen, J; Meijer, E (2000)
We map dilute or semidilute solutions of nonintersecting polymer chains onto a fluid of "soft" particles interacting via a concentration dependent effective pair potential, by inverting the pair distribution function of the centers of mass of the initial polymer chains. A similar inversion is used to derive an effective wall-polymer potential; these potentials are combined to successfully reproduce the calculated exact depletion interaction induced by nonintersecting polymers between two walls. The mapping opens up the possibility of large-scale simulations of polymer solutions in complex geometries.